2005
DOI: 10.1373/clinchem.2005.049742
|View full text |Cite
|
Sign up to set email alerts
|

Use of Protein:Creatinine Ratio Measurements on Random Urine Samples for Prediction of Significant Proteinuria: A Systematic Review

Abstract: Background: Proteinuria is recognized as an independent risk factor for cardiovascular and renal disease and as a predictor of end organ damage. The reference test, a 24-h urine protein estimation, is known to be unreliable. A random urine protein:creatinine ratio has been shown to correlate with a 24-h estimation, but it is not clear whether it can be used to reliably predict the presence of significant proteinuria. Methods: We performed a systematic review of the literature on measurement of the protein:crea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
191
1
14

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 280 publications
(210 citation statements)
references
References 42 publications
4
191
1
14
Order By: Relevance
“…17 Our study also stresses the need for more frequent audit of the operational policies of laboratory and obstetric hospital services and for regular update of patient management protocols in resource-constrained settings in the developing world. 5,8 The results clearly showed that spot urinary protein-creatinine in a pre-24 h urine collection sample is predictive of total urinary protein excretion in hospitalized pregnant women with HDP irrespective of the amount of proteinuria or type of hypertension.…”
Section: Discussionmentioning
confidence: 79%
See 4 more Smart Citations
“…17 Our study also stresses the need for more frequent audit of the operational policies of laboratory and obstetric hospital services and for regular update of patient management protocols in resource-constrained settings in the developing world. 5,8 The results clearly showed that spot urinary protein-creatinine in a pre-24 h urine collection sample is predictive of total urinary protein excretion in hospitalized pregnant women with HDP irrespective of the amount of proteinuria or type of hypertension.…”
Section: Discussionmentioning
confidence: 79%
“…Subjects who have been placed on long-term bed rest at home or strict bed rest in another hospital for more than 36 h before admission were also excluded because of the decreased correlation between the urine protein-creatine ratio and the 24-h urine protein resulting from prolonged recumbency. 2,6,8,16,17 All eligible subjects (n ¼ 95) received written information before enrollment and 90 agreed to enter the study. A spot clean-catch and midstream voided urine sample was collected from each patient for measurement of protein, creatinine and calcium immediately before routine 24-h urine collection.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations